Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/gcc.20305
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal fragile sites FRA3B and FRA16D show correlated expression and association with failure of apoptosis in lymphocytes from patients with thyroid cancer

Abstract: It has been suggested that common fragile sites (cFSs) are related to cancer development. This appears to be the case for FRA3B and FRA16D, localized in two tumor-suppressor genes (FHIT and WWOX, respectively) that are altered by deletions or loss of heterozygosity (LOH) in many cancers. The features responsible for fragility have not yet been identified. Furthermore, it is still unclear whether instability at these regions causes chance deletions and loss of function of the associated genes, or whether the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Motivated by a few recent discoveries [11] about the correlation between two frequently expressed fragile sites, we decided to extend such a correlation analysis to a genome-wide scale. To understand the relevant patterns of correlations on such a large scale a graph theoretical analysis of the network of correlated CFS turned out to be mandatory.…”
Section: Common Fragile Sites In a Systemic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by a few recent discoveries [11] about the correlation between two frequently expressed fragile sites, we decided to extend such a correlation analysis to a genome-wide scale. To understand the relevant patterns of correlations on such a large scale a graph theoretical analysis of the network of correlated CFS turned out to be mandatory.…”
Section: Common Fragile Sites In a Systemic Perspectivementioning
confidence: 99%
“…The data which we used for our analysis are the expression patterns of 137 fragile sites on a sample of 60 subjects reported in [11]. Raw data and experimental procedures to gather them are described in detail in [13] to which we refer the interested reader.…”
Section: The Network Of Co-expressed Cfsmentioning
confidence: 99%
“…This region was also identified as FRA16D: one of the common chromosomal fragile sites (1). For a long time this region was of particular interest, because of the high incidence of loss of heterozygosity (LOH); this was first observed in prostate cancer (2, 3), and later in several other tumor types, including liver cancer (40% LOH) (47), ovarian cancer (8), ductal breast cancer in situ (DCIS) (about 80% LOH) (9), sporadic breast cancer (10), extrahepatic bile ducts (11), esophageal squamous cell carcinoma (12, 13), non-small lung (14), pancreas (15, 16), multiple myeloma (17), thyroid (18), glioblastoma multiforme (19), and Wilms tumors (20–30% LOH) (20). …”
Section: Wwox Tumor Suppressor Gene—discovery and Characteristicsmentioning
confidence: 99%
“…A significant reduction or lack of expression of WWOX gene was observed mainly in breast cancer, but also (amongst other) in esophageal squamous cell carcinomas (12), non-small lung cancers (14, 21), pancreatic tumors (15, 16, 22) prostate, (23), gastric, ovarian (24), thyroid (18, 25), and bladder (26) cancers.…”
Section: Wwox Tumor Suppressor Gene—discovery and Characteristicsmentioning
confidence: 99%
“…There have been reports indicating that Gao and Smith WWOX and cancer 291 the concordant loss of expression of both FHIT (FRA3B) and WWOX (FRA16) blocks apoptosis in lymphocytes in patients with thyroid cancer. 106 Recently, Le Tallec et al performed common fragile site profiling in epithelial and erythroid cells and they found that over 50% of recurrent cancer deletions originate in CFSs that are associated with genes over 300 Kb in size. 69 If the decreased expression of specific large CFS genes is associated with patients' outcome, monitoring the expression of large CFS genes could prove to be a powerful prognostic marker to stratify patients for better treatment options.…”
Section: An Entire Family Of Large Cfs Genesmentioning
confidence: 99%